Implementation of The Pancasila Student Profile Strengthening Project in Developing Environmental Caring Character in Early Childhood in Kindergarten - Clarita Anggana; Mustakimah Mustakimah; Sofa Muthohar (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
Instilling environmental awareness from an early age is a crucial step in shaping a generation that is responsible for nature. This study aims to improve children’s understanding and skills in distinguishing organic and inorganic waste through the use of educational video media and practical activities. This study also aims to develop teacher competencies in implementing the Pancasila Strengthening Student Profile Project (P5) at Hidayatul Mubtadiin Kindergarten. The method used is descriptive qualitative with a field study approach. Data were collected through observation, interviews, and documentation of project activities. The project implementation included the delivery of educational videos on waste awareness, the impact of littering, and how to dispose of organic and inorganic waste. Twenty-two Kindergarten B children participated in a waste sorting activity based on the color of their bins. The results showed that 19 children successfully sorted their waste accurately, while three children experienced difficulties in the learning process. The study concluded that the learning method through educational videos on waste and hands-on practice was effective in improving children's understanding and skills regarding waste and waste management, and supporting the development of environmentally conscious character in early childhood.